2020
DOI: 10.1186/s12969-020-0399-1
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab modifies clinical and laboratory features of macrophage activation syndrome complicating systemic juvenile idiopathic arthritis

Abstract: Background: This study aimed to determine the influence of tocilizumab (TCZ) in modifying the clinical and laboratory features of macrophage activation syndrome (MAS) complicating systemic juvenile idiopathic arthritis (s-JIA). Furthermore, we assessed the performance of the 2016 MAS classification criteria for patients with s-JIA-associated MAS while treated with TCZ. Methods: A panel of 15 pediatric rheumatologists conducted a combination of expert consensus and analysis of real patient data. Clinical and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…As a consequence of the abovementioned pathogenic scenario linking iron, inflammation and infections, there is the need to find a possible therapeutic strategy to prevent CRS and onset of fibrosis occurring particularly in patients with COVID-19. The progress in understanding the critical role of pro-inflammatory cytokines in the pathogenesis of other hyperferritinemic syndromes such as MAS-HLH and AOSD has led to pilot the use of anti-cytokine agents, resulting in an increasing number of successful case reports in patients who were unresponsive to conventional treatments [ 93 ]. The inhibition of IL-1 (with the use of anakinra and canakinumab) and IL-6 (mainly with tocilizumab) showed a strong efficacy compared with placebo in several cohorts and randomized controlled trials in MAS-HLH and AOSD.…”
Section: Iron Depletion Therapymentioning
confidence: 99%
“…As a consequence of the abovementioned pathogenic scenario linking iron, inflammation and infections, there is the need to find a possible therapeutic strategy to prevent CRS and onset of fibrosis occurring particularly in patients with COVID-19. The progress in understanding the critical role of pro-inflammatory cytokines in the pathogenesis of other hyperferritinemic syndromes such as MAS-HLH and AOSD has led to pilot the use of anti-cytokine agents, resulting in an increasing number of successful case reports in patients who were unresponsive to conventional treatments [ 93 ]. The inhibition of IL-1 (with the use of anakinra and canakinumab) and IL-6 (mainly with tocilizumab) showed a strong efficacy compared with placebo in several cohorts and randomized controlled trials in MAS-HLH and AOSD.…”
Section: Iron Depletion Therapymentioning
confidence: 99%
“…Anti-IL-6 treatment with specific blocker tocilizumab has also been suggested effective in attenuating clinical symptoms of MAS. Shimizu et al defined that patients with MAS showed significantly lower ferritin, CRP, triglycerol, fibrinogen, and aspartic aminotransferase serum levels when receiving tocilizumab treatment, indicating an alleviation of systemic inflammation [13]. However, the improvement in clinical and laboratory features of MAS may compromise MAS diagnosis.…”
Section: An Overview Of Mas and Possible Therapiesmentioning
confidence: 99%
“…High ferritin levels are thought to be a biomarker and a driver of disease severity in other clinical disorders characterised by abnormal macrophage activation and elevated IL-6 activity, such as cytokine release syndrome 26 and systemic juvenile idiopathic arthritis (sJIA). 27 In both conditions, patients benefit from tocilizumab treatment, and ferritin levels decrease after treatment in those with sJIA. 27 Although results are hypothesis-generating in this respect, the relationship between hyper-ferritinemia and elevated IL-6 levels in COVID-19 and other diseases provides a potential rationale for why ferritin was predictive for the effects of IL-6 pathway inhibition with tocilizumab in our study.…”
Section: Discussionmentioning
confidence: 99%
“…27 In both conditions, patients benefit from tocilizumab treatment, and ferritin levels decrease after treatment in those with sJIA. 27 Although results are hypothesis-generating in this respect, the relationship between hyper-ferritinemia and elevated IL-6 levels in COVID-19 and other diseases provides a potential rationale for why ferritin was predictive for the effects of IL-6 pathway inhibition with tocilizumab in our study. Additional investigation of biomarkers downstream of IL-6 and ferritin signalling, together with single-cell analysis of pulmonary cells, might further elucidate how high ferritin levels predict benefit from the inhibition of IL-6 activity in patients with severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%